Biportal endoscopic lumbar interbody fusion using a large polyetheretherketone cage: preliminary results - Sang-Min Park; Hyun-Jin Park; Ki-Han You; Ho-Joong Kim; Jin S. Yeom (Asian Spine Journal)
Study Design Retrospective study. Purpose This study aimed to introduce biportal endoscopic lumbar interbody fusion (BELIF) using a large polyetheretherketone (PEEK) cage, describe the surgical technique, and evaluate its clinical and radiological outcomes. Overview of Literature Biportal endoscopic techniques have emerged as a promising approach in spine surgery, and BELIF is reported to have good surgical outcomes. The use of large PEEK cage in lumbar interbody fusion has gained attention owing to their potential biomechanical advantages. Despite the potential benefits of BELIF with large PEEK cages, studies on its effectiveness and safety are lacking. Methods Twelve consecutive patients underwent single-level BELIF for lumbar degenerative disease. The technique involves two small portals, one each for endoscopy and instruments. A large PEEK cage was inserted through a posterolateral approach. Clinical outcomes, including a Visual Analog Scale for back and leg pain, the Oswestry Disability Index, and the European Quality of Life-5 Dimensions, were assessed preoperatively and at 3, 6, and 12 months postoperatively. Fusion status was evaluated using computed tomography (CT) at 12 months. Results The mean patient age was 69.1±7.2 years, with operations predominantly at the L4–5 level (83%). The mean operation time was 149.7±37.4 minutes, and the average surgical drainage was 201.4±59.7 mL. All clinical outcome measures showed significant improvement at 12 months (p<0.05). Fusion was achieved in 83.3% of patients. Cage subsidence (>1 mm) occurred in one patient (8.3%). Complications included one case each of incidental durotomy, wrong-site surgery, and wound dehiscence and three cases of asymptomatic hematoma. Conclusions BELIF using a large PEEK cage demonstrated promising clinical outcomes and fusion rates. The technique offers enhanced visualization and enables direct neural decompression while minimizing tissue trauma. The use of a large PEEK cage may contribute to improved stability and reduced subsidence risk.